2009
DOI: 10.1111/j.1439-0531.2007.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GnRH Dose on Occurrence of Short Oestrous Cycles and LH Response in Cyclic Dairy Heifers

Abstract: Prostaglandin F(2 alpha) (PGF(2 alpha)) and GnRH treatments given 24 h apart have been shown to result in short oestrous cycles (8-12 days) in some cows and heifers. The differences in responses may depend on the dose of GnRH. Therefore, the effect of the dose of GnRH on occurrence of short cycles and LH response was studied here. Oestrus was induced with dexcloprostenol (0.15 mg) in two groups of Ayrshire heifers. A second luteolysis was induced similarly on day 7 after ovulation; 24 h after PGF(2 alpha) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
2
1
0
Order By: Relevance
“…The 48-h interval between GnRH injections in Chenault et al (1990) may have precluded a full pituitary response to GnRH in heifers previously receiving a desensitizing dose of some of the GnRH analogs. It is also intriguing that a lack of difference was observed in LH secretion in Holstein heifers receiving 100 compared with 500 μg of gonadorelin 24 h after a luteolytic dose of a synthetic PGF 2α analog (Rantala et al, 2009). Conversely, in agreement with our results, Dias et al (2010) reported that beef heifers treated with 200 μg of gonadorelin when mean P4 concentration was 6 to 7 ng/mL had greater mean LH concentration at 1 and 2 h after treatment than heifers receiving 100 μg of GnRH.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The 48-h interval between GnRH injections in Chenault et al (1990) may have precluded a full pituitary response to GnRH in heifers previously receiving a desensitizing dose of some of the GnRH analogs. It is also intriguing that a lack of difference was observed in LH secretion in Holstein heifers receiving 100 compared with 500 μg of gonadorelin 24 h after a luteolytic dose of a synthetic PGF 2α analog (Rantala et al, 2009). Conversely, in agreement with our results, Dias et al (2010) reported that beef heifers treated with 200 μg of gonadorelin when mean P4 concentration was 6 to 7 ng/mL had greater mean LH concentration at 1 and 2 h after treatment than heifers receiving 100 μg of GnRH.…”
Section: Discussionsupporting
confidence: 87%
“…A potential strategy to enhance GnRH-induced LH release in lactating dairy cows may be to increase the dose of GnRH administered. Studies in cattle have reported diverse results using different doses of GnRH with either enhanced or similar LH release in response to increasing doses of GnRH (Chenault et al, 1990;Yamada et al, 2002;Colazo et al, 2009;Rantala et al, 2009;Souza et al, 2009;Dias et al, 2010). Much of the variation in these results may be attributed to factors associated with the experimental design of these studies, including the type and physiological conditions of the animals used, variations among GnRH products, GnRH doses administered, LH assay methods, parameters used to compare LH secretion, and the steroid milieu at the time of GnRH treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, cows that had a surge of LH during the sampling period tended to ovulate earlier, and timing of ovulation for cows that ovulated in the G100-IM, G1000CA, and B80CA was within the expected time frame after GnRH treatment (Pursley et al, 1995;Rantala et al, 2009;Giordano et al, 2012a). In spite of the fact that cows in the G1000CA and B80CA treatments had a longer interval until LH concentrations reached their peak, mean time to ovulation was the same in all treatments.…”
supporting
confidence: 64%